CAPitalising on conservation knowledge: Using Conservation Action Planning, Healthy Country Planning and the Open Standards in Australia. (19th June 2017) - Carr, Ben; Fitzsimons, James; Holland, Natalie; Berkinshaw, Todd; Bradby, Keith; Cowell, Stuart; Deegan, Paula; Koch, Paul; Looker, Michael; Varcoe, Tony; Walsh, Philippa; Weisenberger, Frank
Abstract : More than 20 organisations use Conservation Action Planning (CAP), Healthy Country Planning and the Open Standards for the Practice of Conservation in over 140 projects, covering almost 160 million ha across Australia. This review documents the history, evolution and application of CAP in Australia and discusses its strengths, limitations and lessons learnt by users, including conservation planners, practitioners and policymakers.